Making WTO Dispute Settlement System Useful for LDCs - Ingnam, Kumar (Kathmandu School of Law Review, 2018)
The World Trade Organization, a forum of multinational bargaining for trade under an international regulatory authority, has adhered compromising provisions for all member countries. The natural rule ‘stronger pie more and weaker are hanged up in the better dream of future' is indirectly reflected in the WTO rules (the agreements, commitments and a few decisions of Ministerial Conferences) as well. While weaker countries (including independent economic territories) had shown strong reservation in opening up Agreement on Trade-Related Aspects of Intellectual Property Rights, General Agreement on Trade in Services and Agricultural market during negotiation, the richer had persuaded in inserting scattered, flexible and concessional provisions in different Agreements of WTO; and Ministerial Conferences had made decisions and commitments to support and compensate them. The ultimate indication of trade performance is measured on their transactions and on the free movement of their goods and services. In case if the treatment is not fair or the regulatory compliance is not fulfilled, remedy ought to be accessible. Since its commencement, just a single case was initiated by Least Developed Countries for settlement through the Dispute Settlement Body due to the doubt on the procedure and effectiveness of DSB. The article tries to analyze that why weaker (especially LDCs) countries are reluctant in joining DSB and framing way-out to resolve the problem by making convenient provisions for the weaker, LDCs as well.